A self-healing cementitious composite with mineral admixtures and built-in carbonate. (September 2018) - Wang, Xianfeng; Fang, Cheng; Li, Dawang; Han, Ningxu; Xing, Feng
Abstract: In this study, experimental investigations were conducted on the self-healing potential of concrete. Sulfoaluminate based expansive agents (CSA), crystalline admixture (CA), and calcium hydrogen phosphate were used as part of cementitious materials, and porous ceramsites served as the carrier for sodium carbonate solution. The quantification of the widths/areas of the cracks was performed to examine the feasibility of the approach and optimize mix proportions. A gas permeability test was conducted on two preferred mixes to investigate the change in the gas permeability of pre-cracked samples. After curing in still water for 28 d, the pre-cracked specimens with ceramsites containing sodium carbonate, and appropriate dosages of additives exhibited considerable efficiency in surface crack closure and healing in gas permeability. The SEM results indicated the deeper formation of healing products (CaCO3 ) in the cracks of the suggested mix when compared to that in the control mix. A healing mechanism was discussed based on the experimental results.